2016
DOI: 10.1039/c5ra26156b
|View full text |Cite
|
Sign up to set email alerts
|

DFT insights into the cycloisomerization of ω-alkynylfuran catalyzed by planar gold clusters: mechanism and selectivity, as compared to Au(i)-catalysis

Abstract: A detailed reaction mechanism of the triatomic gold cluster-catalyzed cycloisomerization of u-alkynylfuran was systemically investigated via density functional theory at the TPSSh/def2-TZVP level. The computational results indicated that the 5-exo Friedel-Crafts-type mechanism is the most favorable mechanism to form the phenol derivatives. The strong interaction between the gold and vinyl fragments in the Friedel-Crafts adduct is essential for the priority of the 5-exo Friedel-Crafts-type mechanism. Then, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Herein, u-alkynylfuran cycloisomerisation catalyzed by CeO 2 -supported gold nanoparticles (Au 3 , Au 4 , Au 10 , Au 11 ) is explored with the help of density functional theory (DFT), as an expansion of our prior research. [37][38][39] Gold nanoparticles (Au 3 , Au 4 , Au 10 , Au 11 ) were employed for consistence with experimental results reported by Oliver-Meseguer et al and others. [40][41][42] In these studies, it was found that small gold clusters (only 3 to 10 atoms in size) can be formed during the catalytic processes, which can catalyze the ualkynylfuran cycloisomerisation reaction.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Herein, u-alkynylfuran cycloisomerisation catalyzed by CeO 2 -supported gold nanoparticles (Au 3 , Au 4 , Au 10 , Au 11 ) is explored with the help of density functional theory (DFT), as an expansion of our prior research. [37][38][39] Gold nanoparticles (Au 3 , Au 4 , Au 10 , Au 11 ) were employed for consistence with experimental results reported by Oliver-Meseguer et al and others. [40][41][42] In these studies, it was found that small gold clusters (only 3 to 10 atoms in size) can be formed during the catalytic processes, which can catalyze the ualkynylfuran cycloisomerisation reaction.…”
Section: Introductionmentioning
confidence: 89%
“…4-7, the rate-limiting step of the 5-exo FCT reaction route in the gas phase is the nucleophilic addition of the Cb atom to the C1 site of the furan ring to form the spiro-intermediate IM2, which has an energy barrier of 13.66 kcal mol À1 , while the formation of IM4 is the rate-determining step in acetonitrile. However, for the DDA pathway, the formation of the b-alkenylated furan and the 6-endo FCT pathway, the energy barriers of the rate-limiting steps are 46 On the basis of our previous reports [37][38][39] and the above discussions, the 5-exo Friedel-Cras-type mechanism (FCT) is the most feasible pathway for u-alkynylfuran cycloisomerisation. Accordingly, the 5-exo FCT mechanism of u-alkynylfuran cycloisomerisation on the various reaction sites of Au 10 / CeO 2 (111) and Au 11 /CeO 2 (111) were investigated.…”
Section: The Possible Mechanisms For U-alkynylfuran Cycloisomerisatiomentioning
confidence: 95%
See 1 more Smart Citation
“…We also investigated the full reaction mechanism of ω‐alkynylfuran cycloisomerization using Au 38 as the catalyst . In addition, the planar gold clusters were chosen as models, which are used for catalyzing the ω‐alkynylfuran cycloisomerization . However, to the best of our knowledge, a theoretical understanding of the ω‐alkynylfuran cycloisomerization mechanism on the bimetallic core–shell nanoclusters is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…[47] In addition, the planar gold clusters were chosen as models, which are used for catalyzing the w-alkynylfuran cycloisomerization. [48] However,t o the besto fo ur knowledge,atheoreticalu nderstanding of the w-alkynylfuran cycloisomerization mechanism on the bimetallic core-shell nanoclusters is still lacking.T oa chieve this goal and extend the previous work, we herein present DFT calculations to predict the catalytic activities of the M 6 @Au 32 core-shell nanoclusterst oward the w-alkynylfuran cycloisomerization. The Au 38 nanocluster wasc hosen as the catalyst model and was regarded as the template used ford esigning the M 6 @Au 32 coreshell nanoclusters by substitution of the core Au atoms.…”
Section: Introductionmentioning
confidence: 99%